Natalia Ginzburg : a voice of the twentieth century - Jeannet, Angela M.; Katz, Giuliana, 1938- (Toronto Italian studies., 2000)
A prominent and prolific Italian writer, Natalia Ginzburg (1916-1991) is known for her novels, plays, short stories, and essays. This collection brings together, for an English-speaking audience, a variety of critical perspectives on Ginzburg's work. The essays, all by North American scholars, examine the author's entire production. The topics examined include Ginzburg's struggle to define herself as a woman, a writer, and an intellectual; her interpretation of the relationship between historical events and private lives; her reflections on the women's movement and the changing nature of the family; and her mastery of a distinctly personal writing style. What emerges here is a nuanced and complex portrait of Ginzburg and her work. The reader is given a sense of the importance of her contribution, not only as a writer but as a witness to the events of the twentieth century. The volume also includes a chronology, a bibliography, and translations of some of Ginzburg's lesser-known writings, including three articles, a poem, and a one-act play.